Предмет: Алгебра,
автор: sapasheva2002
m^3 - m - am^2 + a
Разложите на множители
Ответы
Автор ответа:
0
M^3 - m - am^2 + aРазложите на множители.
И так получается :
-(a-m) (-1+m) (1+m)
И так получается :
-(a-m) (-1+m) (1+m)
Автор ответа:
0
= ( M^3 - AM^2 ) - ( M - A ) = M^2 * ( M - A ) - ( M - A ) = ( M - A)*( M^2 - 1 ) =
= ( M - A)*( M - 1)*( M + 1 )
= ( M - A)*( M - 1)*( M + 1 )
Похожие вопросы
Предмет: Английский язык,
автор: aruzantogzanova801
Предмет: Английский язык,
автор: Аноним
Предмет: Қазақ тiлi,
автор: azhakon168
Предмет: Математика,
автор: iyayuyu
Предмет: Биология,
автор: MixGamePro